How products induce regulatory fit: evidence from the health domain. Issue 6 (14th September 2015) - Borges, Adilson; Gomez, Pierrick
Abstract : Purpose: – The purpose of this paper is to test whether the simple exposure to different types of products can trigger different motivational orientation on consumers (prevention vs promotion), which in turn would match message frame and increase persuasion. Design/methodology/approach: – Three experiments test whether exposure to product categories can trigger consumer's regulatory focus orientation. Participants in the pilot study are students, while participants in the two other studies are consumers. Findings: – A first pilot study randomly exposed participants to a product that could trigger promotion orientation (e.g. orange juice) versus a product that could trigger prevention orientation (e.g. sunscreen). Participants exposed to promotion (prevention) product suggest more promotion (prevention) strategies to reach a particular goal (preparing for their final exam). Study 2 shows that gain (vs loss)-framed messages using health appeals have better evaluations when featuring promotion (vs prevention) products. Study 3 generalizes these results using another sample and different product categories. Research limitations/implications: – The paper uses some product categories and including other categories would increase external validity. Practical implications: – The practical implication is to help marketers to choose the right health argument to match the product category they are trying to sell. Originality/value: – Theoretically, the results from three studies show that exposure to products can temporarily trigger a consumer's regulatory focus and that messages using health arguments that are consistent with this regulatory focus are more persuasive than those that are not. Managerially, these results help managers to adapt the right message in function of the product category.